2005
DOI: 10.1016/j.physletb.2005.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Gamow–Teller quenching factor from charge exchange reactions on 90Zr

Abstract: Double differential cross sections between 0 • -12 • were measured for the 90 Zr(n, p) reaction at 293 MeV over a wide excitation energy range of 0-70 MeV. A multipole decomposition technique was applied to the present data as well as the previously obtained 90 Zr(p, n) data to extract the Gamow-Teller (GT) component from the continuum. The GT quenching factor Q was derived by using the obtained total GT strengths. The result is Q = 0.88 ± 0.06, not including an overall normalization uncertainty in the GT unit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 33 publications
7
94
0
Order By: Relevance
“…The quenching factor depends on the nucleus, with q 2 ≈ 0.84 − 0.92 due to 2BCs for the studied nuclei. We recall that q 2 ≈ 0.88 − 0.92, extracted from experiments on 90 Zr [18][19][20], are within our error band. We also computed the low-lying strengths for β − decay, and found that only 70% -80% of the total strength S ± is exhausted below 10 MeV of excitation energy.…”
Section: Gamow-teller Operatorsupporting
confidence: 69%
See 1 more Smart Citation
“…The quenching factor depends on the nucleus, with q 2 ≈ 0.84 − 0.92 due to 2BCs for the studied nuclei. We recall that q 2 ≈ 0.88 − 0.92, extracted from experiments on 90 Zr [18][19][20], are within our error band. We also computed the low-lying strengths for β − decay, and found that only 70% -80% of the total strength S ± is exhausted below 10 MeV of excitation energy.…”
Section: Gamow-teller Operatorsupporting
confidence: 69%
“…GamowTeller strength functions [14,15] are of particular interest also because of their astrophysical relevance [16]. Chargeexchange measurements on 90 Zr and other medium mass nuclei have suggested that the total strength for β decay is quenched by a factor of q 2 ≈ 0.88 − 0.92 [17][18][19][20] when compared to the Ikeda sum rule [21]. Similarly, shellmodel calculations [22,23] suggest that g A needs to be quenched by a factor q ≈ 0.75 to match data.…”
mentioning
confidence: 99%
“…These experiments, however, were only able to measure the strength up to the excitation energy of the giant resonance. A consistent analysis of (p, n) and (n, p) reaction data from 90 Zr over a much wider range of excitation energies, concluded that the GT strength is actually quenched by approximately 10% [5,6]. Theoretical models systematically overestimate the transition strength compared to the measured values [7].…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, recent experiments reported data on the Gamow-Teller response in 90 Zr, in both β − [5] and β + channels [6], up to 50 MeV excitation energies. Therefore, in the total strength, contributions from higher-order terms in the expansion in q appear, the first of which is the isovector spin monopole (IVSM) mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation